Too much social media? Unveiling the effects of determinants in social media fatigue - Qin, Can; Li, Ying; Wang, Tian; Zhao, Jing; Tong, Ling; Yang, Jiawei; Liu, Yuyin (Frontiers in Psychology, 2024)
Introduction With the boom in social media, many people spend a lot of time on these platforms. Among them, some developed negative emotions, such as fatigue, depression, or disinterest in communicating, and used social media temporarily or permanently. Therefore, this study aims to explore the antecedents of social media fatigue, including social media helpfulness, social media self-efficacy, online subjective well-being, social comparison, compulsive social media use, privacy concerns, fear of missing out, and information overload, and to further discuss the determinants of social media fatigue on social anxiety and lurking. Methods An online questionnaire was distributed to social media users, and 659 valid samples were obtained with the help of a purposive sampling strategy. The data was analyzed by the partial least square (PLS) method. Results The study found that social media self-efficacy had a significant negative effect on social media fatigue; compulsive social media use, fear of missing out, and information overload had a significant positive effect on social media fatigue; and social media fatigue had a significant positive effect on social anxiety and lurking. Discussion The research results can be used as a reference for social media marketers and internet service providers in developing business strategies.